1997
DOI: 10.1111/j.1096-3642.1997.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of locomotion in the caecilians Dermophis mexicanus and Typhlonectes natans (Amphibia: Gymnophiona)

Abstract: We compared locomotion of two species of caecilian using x-ray videography of the animals traversing smooth-sided channels and a pegboard. Two channel widths were used, a body width channel and a body width + 20°/o channel. The terrestrial caecilian, Demophis mexicanus, used internal concertina locomotion in both channels and lateral undulation on the pegboard. The aquatic caecilian, lyhlonectes natans, was not able to move at all in the body width channel. In the wider channel 7yhlonectes proceeded at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…Precisely how these movements are achieved in S. stimpsoni is difficult to evaluate from our ventral-view video footage. The close attachment of the skin to the underlying musculature and, thereby, to the vertebral column in most fishes (Wainwright, Vosburgh & Hebrank, 1978) suggests that the use of internal concertina mechanisms (similar to those used by some caecilians: Summers & O'Reilly, 1997) is unlikely. An 'inch-worm' mechanism (with dorsoventral flexion) seems a more viable possibility, but it is unclear how this would be controlled.…”
Section: Structures Contributing To Propulsion In Powerburst and Inchmentioning
confidence: 99%
“…Precisely how these movements are achieved in S. stimpsoni is difficult to evaluate from our ventral-view video footage. The close attachment of the skin to the underlying musculature and, thereby, to the vertebral column in most fishes (Wainwright, Vosburgh & Hebrank, 1978) suggests that the use of internal concertina mechanisms (similar to those used by some caecilians: Summers & O'Reilly, 1997) is unlikely. An 'inch-worm' mechanism (with dorsoventral flexion) seems a more viable possibility, but it is unclear how this would be controlled.…”
Section: Structures Contributing To Propulsion In Powerburst and Inchmentioning
confidence: 99%
“…In these elongate fish species, points do not always follow the exact same path, body regions sometimes appear to slide unexpectedly and movements occasionally appear uncoordinated. Some previous studies have used pegboards to elicit lateral undulation (Bennet et al, 1974;Jayne, 1986;Gans and Gasc, 1990;Summers and O'Reilly, 1997), and this structured environment may constrain study organisms to move in a more predictable fashion. However, some of these differences in movement between fish and snakes are probably due, at least in part, to differences in musculature and morphology.…”
Section: Do Distantly Related Amphibious Fishes Demonstrate Similar Mmentioning
confidence: 99%
“…Vermiform bending movements of the vertebral column and associated axial muscles occur independently of (and within) the sheath of skin and more super®cial trunk muscles. Summers and O'Reilly (1997) concluded that this form of locomotion was present in the last common ancestor of crown-group caecilians. If so, then the extended basapophyseal processes may characterise crown-group taxa and their immediate ancestors.…”
Section: Comparisonmentioning
confidence: 99%